From structure topology to chemical composition. XXIII. Revision of the crystal structure and chemical formula of zvyaginite, Na2ZnTiNb2(Si2O7)2O2(OH)2(H2O)4, a seidozerite-supergroup mineral from the Lovozero alkaline massif, Kola peninsula, Russia. (1st December 2017) - Sokolova, E.; Genovese, A.; Falqui, A.; Hawthorne, F.C.; Cámara, F.
The crystal structure and chemical formula of zvyaginite, ideally Na2ZnTiNb2(Si2O7)2O2(OH)2(H2O)4, a lamprophyllite-group mineral of the seidozerite supergroup from the type locality, Mt. Malyi Punkaruaiv, Lovozero alkaline massif, Kola Peninsula, Russia have been revised. The crystal structure was refined with a new origin in space group C1, a = 10.769(2), b = 14.276(3), c = 12.101(2) Å, α = 105.45(3), β = 95.17(3), γ = 90.04(3)°, V = 1785.3(3.2) Å3, R1 = 9.23%. The electron-microprobe analysis gave the following empirical formula [calculated on 22 (O + F)]: (Na0.75Ca0.09K0.041.12)∑2 (Na1.12Zn0.88Mn0.17Fe2+0.040.79)∑3 (Nb1.68Ti1.25Al0.07)∑3 (Si4.03O14)O2 [(OH)1.11F0.89]∑2 (H2O)4, Z = 4. Electron-diffraction patterns have prominent streaking along c* and HRTEM images show an intergrowth of crystalline zvyaginite with two distinct phases, both of which are partially amorphous. The crystal structure of zvyaginite is an array of TS (Titanium-Silicate) blocks connected via hydrogen bonds between H2O groups. The TS block consists of HOH sheets (H = heteropolyhedral, O = octahedral) parallel to (001). In the O sheet, the [6]MO(1, 4, 5) sites are occupied mainly by Ti, Zn and Na and the [6]MO(2, 3) sites are occupied by Na at less than 50%. In the H sheet, the [6]MH(1, 2) sites are occupied mainly by Nb and the [8]AP(1) and [8]AP(2) sites are occupied mainly by Na and . The MH and AP polyhedra and Si2O7 groups constitute the H sheet. The ideal structural formula is Na Nb2 NaZn Ti(Si2O7)2O2(OH)2(H2O)4. Zvyaginite is a Zn-bearing and Na-poor analogue of epistolite, ideally (Na)Nb2Na3Ti(Si2O7)2O2(OH)2(H2O)4. Epistolite and zvyaginite are related by the following substitution in the O sheet of the TS-block: (Na+2)epi ↔ Zn2+zvy + zvy. The doubling of the t1 and t2 translations of zvyaginite relative to those of epistolite is due to the order of Zn and Na along a (t1) and b (t2) in the O sheet of zvyaginite.